Exigent psychoanalysis : the interventions of Jean Laplanche - Ashtor, Gila (Milton Park, Abingdon Oxon ; New York, NY : Routledge, 2022)
"Exigent Psychoanalysis: The Interventions of Jean Laplanche offers a bold exploration of the contemporary psychoanalytic field by focusing on key issues through the lens of one of this century's most exacting and invigorating psychoanalytic theorists. Deliberately taking an integrative approach that spans a vast range of psychoanalytic ideas - with particular focus on the enduring tension between Freudian and Relational paradigms - Ashtor shows how a rigorous close reading of Laplanche's work can disrupt stale binaries and forge new possibilities for revolutionizing the foundations of psychoanalysis. Organized as pointed interventions on such topics as metapsychology, motivation, the unconscious and psychic structure, Ashtor integrates cutting edge research on Affect theory and sexuality to demonstrate the potential for fieldwide innovation. Of interest to established and emerging clinicians alike and aimed at addressing a broad spectrum of theoretical positions, Exigent Psychoanalysis offers the first extensive clinical and theoretical study of Laplanche's work, thus facilitating a timely and cutting-edge intervention in contemporary psychoanalytic debates"--
Metapsychology: mytho-symbolic versus metapsychology -- Sexuality: Laplanche's theory of the unconscious -- Seduction: Laplanche's theory of psychic structure -- Translation: Laplanche's theory of motivation.
Keywords: Laplanche, Jean; Psychoanalysis; PSYCHOLOGY / Movements / Psychoanalysis; PSYCHOLOGY / Mental Health